2017
DOI: 10.32463/rphs.2018.v04i01.06
|View full text |Cite
|
Sign up to set email alerts
|

Nurse’s knowledge and Awareness Regarding Cervical Cancer and its Prevention in Different Hospitals of Quetta, Pakistan

Abstract: Objective: This study aimed to assess the knowledge and awareness regarding cervical cancer and its prevention among nurses working in different hospitals of Quetta, Pakistan. Methodology: The cross sectional, descriptive study was conducted by using structured questionnaire in different hospitals of Quetta from January to September 2016. Convenient sampling technique was applied by targeting all the nurses working in different hospitals of Quetta city. Study questionnaire was developed and tested for validit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
2
2
Order By: Relevance
“…However, knowledge was lower in our study compared to studies conducted in Ethiopia (86.9%) [54], India (85%) [63], Nigeria (98.6%) [58], Pakistan (88.1%) [64] and Burundi (76.3%) [55]. Unlike our study in which participants had to score at least 18 or more out of 25, the study conducted in India categorised participants as having good knowledge if participants were able to provide any three correct known risk factors for cervical cancer [63].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…However, knowledge was lower in our study compared to studies conducted in Ethiopia (86.9%) [54], India (85%) [63], Nigeria (98.6%) [58], Pakistan (88.1%) [64] and Burundi (76.3%) [55]. Unlike our study in which participants had to score at least 18 or more out of 25, the study conducted in India categorised participants as having good knowledge if participants were able to provide any three correct known risk factors for cervical cancer [63].…”
Section: Discussioncontrasting
confidence: 87%
“…Unlike our study in which participants had to score at least 18 or more out of 25, the study conducted in India categorised participants as having good knowledge if participants were able to provide any three correct known risk factors for cervical cancer [63]. The studies conducted in Ethiopia [54], Nigeria [58] and Pakistan [64] all used scores of 50% or more to categorise participants as having good knowledge. The study conducted in Burundi had participants who were general medical practitioners [55] and are expected to have better knowledge due to their training on cervical cancer than the participants in our study who had lower levels of professional training.…”
Section: Discussionmentioning
confidence: 96%
“…When compared with the study conducted with healthcare professionals in the Ivory Coast, it was seen that the cervical knowledge score of the participants (55.7%) was lower than our study [ 21 ]. However, other studies that were Ethiopia (86.9%) [ 15 ], India (85%) [ 27 ], Nigeria (98.6%) [ 28 ], Pakistan (%88.1) [ 29 ] and Burundi's (76.3%) was found higher than our study [ 30 ]. It was found that the cervical score averages of the studies carried out were higher.…”
Section: Discussioncontrasting
confidence: 91%
“…At the hospital level, equal access to information for women across all sociodemographic strata through educational videos in the waiting areas outside the outpatient clinic, and group and one-on-one counselling on the importance of cervical cancer screening could be effective [42]. Lessons can be learned from various behavior change communication interventions for cervical cancer globally to enhance the strategies to raise awareness for cervical cancer in Nepal [43][44][45].…”
Section: Discussionmentioning
confidence: 99%